2018
DOI: 10.1186/s40497-018-0132-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing micro and small enterprise’s decision to innovate in Kenya

Abstract: An enterprise's propensity to innovate has been recognised to have an important bearing on its performance. In Kenya empirical work on micro and small enterprises (MSEs) propensity to innovate is still nascent in spite of the pivotal role played by these enterprises in the economy. The current paper used a Probit econometric model to analyse factors that influence MSE's decision to innovate or not. Results from the analysis show that the average number of years of education for a production worker, physical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…This may be….. This result is consistent with the findings of the studies of Szczepanska-Woszczyna (2014); Talegeta (2014), Zajkowska(2015) and Njiraini et al(2018) Business location is positively and significantly affecting innovative practice of MSEs the 1% level of significance as it can be noted in the table 4.5 above. The estimated odd ratio of MSEs which were established near to the supplier/customer was 0.126..This implies that the probability of MSEs which were located near to their suppliers/customers is 0.011 times more likely be innovative controlling for the other covariates in the model.…”
Section: Binary Logistics Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This may be….. This result is consistent with the findings of the studies of Szczepanska-Woszczyna (2014); Talegeta (2014), Zajkowska(2015) and Njiraini et al(2018) Business location is positively and significantly affecting innovative practice of MSEs the 1% level of significance as it can be noted in the table 4.5 above. The estimated odd ratio of MSEs which were established near to the supplier/customer was 0.126..This implies that the probability of MSEs which were located near to their suppliers/customers is 0.011 times more likely be innovative controlling for the other covariates in the model.…”
Section: Binary Logistics Resultssupporting
confidence: 89%
“…The estimated odd ratio of MSEs which were engaged in research was 0.861.This implies that the probability of MSEs which were engaged in research is 0.0861 times more likely be innovative controlling for the other covariates in the model. This result is in line with Szczepanska-Woszczyna (2014); Talegeta (2014) and Zajkowska(2015) and Njiraini et al(2018).…”
Section: Binary Logistics Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…They found that all the indicators of human capital in the mining industry were important in determining the outcome of innovations in the industry. However, contrary to most studies, Njiraini et al. (2018) , using data from the World Bank Enterprise Survey (ES) and the Innovation Follow-up Survey (2013), found that manager's experience acted as a hindrance towards micro, small and medium-sized enterprise (MSME)s’ decision to innovate in Kenya.…”
Section: Review Of the Related Literature And Hypotheses Developmentmentioning
confidence: 77%
“…Existing literature reveal three types of relations among human capital, innovation and organisational performance. 1) the positive relation between top managers' human capital and innovation ( Azeem and Baker, 2020 ; Jegede et al., 2016 ; Njiraini et al., 2018 ; Vixathep and Phonvisay, 2019 ), 2) the positive relation between innovation and firm productivity ( Cin et al., 2017 ; Exposito and Sanchis-Llopis, 2018 ; Nyeadi et al., 2018 ; Vixathep and Phonvisay, 2019 ) and 3) the positive relation between human capital and firm productivity ( Aggrey et al., 2010 ; Blundell et al., 1999 ; Okumu and Mawejje, 2019 ; Onkelinx et al., 2016 ; Rukumnuaykit and Pholphirul, 2015 ; Tan et al., 2016 ). To the best of the author's knowledge, however, the three relations have not been examined simultaneously, especially in an African (developing country) context.…”
Section: Introductionmentioning
confidence: 99%